Complete and robust bandgap switching in double-inverse-opal photonic crystals - Aryal, D.P.; K. L. Tsakmakidis; Jamois, C.; Hess, O. (Applied Physics Letters, 2008)
The authors theoretically demonstrate a practical scheme for robust and complete photonic bandgap switching using a three-dimensional double-inverse-opal photonic crystal. The investigated structure consists of a close-packed face-centered-cubic arrangement of spherical air pores, interconnected via air channels and embedded in a high-index (tin disulfide) backbone. We show that by placing lower-index movable dielectric scatterers (titania) inside the air pores, a complete photonic bandgap opens for certain positions of the scatterers, which altogether closes for other positions. Our analysis reveals that this switching scheme is robust to geometric imperfections and allows for sizeable bandgap switching. © 2008 American Institute of Physics.
cited By 4